Synthesis and Herbicidal Activity of Amide Derivatives Containing Thiazole Moiety - Weng, Jian-Quan; Liu, Xing-Hai; Tong, Guo-Tong (Asian Journal of Chemistry, 2012)
Twelve novel amide derivatives containing thiazole moiety were synthesized via a coupling reaction of [4-(substituted phenyl)thiazol-2-yl] acetonitrile and aryl isocyanates catalyzed by organic bases. Their structures were characterized by 1H NMR, FTIR, MS and elemental analysis. The preliminary bioassay indicated that these compounds exhibited moderate herbicidal activities against Echinochloa crusgalli and Amaranthus ascedense.